Quality of Life Analysis During Transition From Stationary to Portable Infusion Pump in Home Parenteral Nutrition Patients: A Canadian Experience. (17th December 2013) - Saqui, Olivia; Fernandes, Gail; Allard, Johane P.
Abstract : Background: Quality of life (QOL) of patients receiving home parenteral nutrition (HPN) may be impacted by device technology. Historically, our HPN patients used pole‐mounted pumps which can hinder activities and affect QOL. Methods : Patients receiving HPN with a pole‐mounted pump completed Short Form 36 (SF‐36®) and pump‐specific questionnaires. Patients were then enrolled in a 2‐month prospective crossover open study. Patients were randomized to use a pole‐mounted pump or a portable pump. After 1 month, each arm crossed over. Measurements were repeated at 4 and 8 weeks. Results : Participants included 5 males, 15 females; age 52.8 ± 3.3 (mean ± SEM) years; 50% had short bowel syndrome; received HPN for 83.3 ± 15.9 months; infused HPN over 11.2 ± 0.3 hours/day; 4.3 ± 0.4 days/week. Portable pump users scored 53.75 ± 5.64, 61.25 ± 6.14, and 40.31 ± 4.94 in SF‐36v2 physical, social, and health vitality, respectively, while the stationary pump users scored 45.50 ± 4.82, 55.00 ± 5.97, and 35.31 ± 4.63, respectively (NS). They reported ease of movement between rooms (4.11 ± 0.21 vs 1.44 ± 0.20; P = .001); when traveling (5.00 ± 0.00 vs 3.00 ± 0.45; P < .02) (1 = very difficult, 5 = very easy ); 5.0% were sleep disturbed with the portable compared to 42.1% with pole‐mounted pump ( P < .04). Overall, patients were significantly happier with the portable vs pole‐mounted pump (4.53 ± 0.19 vs 2.68 ± 0.22; P < .001) (1 = very unhappy, 5 = very happy ). Conclusion : Our HPN patients reported improved happiness and satisfaction regarding ease of use and function with a portable vs pole‐mounted pump